Clinical value of imaging for lymph nodes evaluation with particular emphasis on ultrasonography - Chiorean, L.; Cui, X. W.; Klein, S. A.; Budjan, J.; Sparchez, Z.; Radzina, M.; Jenssen, C.; Dong, Y.; Dietrich, C. F. (Zeitschrift für Gastroenterologie, 2016)
Enlarged or irregular lymph nodes (LNs) are clinical and imaging findings in a large variety of malignant and non-malignant diseases. A comprehensive diagnostic work up is usually necessary in order to differentiate the benign or the malignant nature of the altered LNs. The diagnosis has to be made using all clinical information and, if necessary, assessed LNs need to be biopsied and further, histologically or microbiologically characterized. However, imaging techniques, and particularly ultrasonography (US), are essential on the way to the final diagnosis, from initial detection and characterization to follow-up of biopsy guidance. Computed-tomography (CT) and/or magnetic resonance imaging (MRI) are of great value for oncological diseases staging and treatment monitoring. Imaging techniques are helpful in distinguishing between benign and malignant LNs disease as well as between LNs metastases and lymphoma in most cases. Furthermore, imaging can define the extent and distribution of malignant diseases. It may assist, through the use of particular techniques such as elastography, to identify the most suspicious LN to be biopsied and to guide targeted biopsies from the most suspicious areas. It also serves as the main tool for the evaluation of treatment response in malignant diseases. The quality of LNs imaging has remarkably improved in recent years. New methods, such as contrast-enhanced ultrasonography (CEUS), elastography, positron emission tomography (PET)/PET-CT, as well as diffusion weighted imaging (DWI) in MRI, have already led to substantial changes in clinical practice. This review describes the most recent imaging techniques for LNs assessment, and their particular clinical value, with a special emphasis on the role of US techniques. Strengths and weaknesses of different imaging tools are discussed comprehensively, highlighting the importance of a corroborative attitude for successful management of each particular case.
Keywords: Bildgebung; kontrastverstärkte Sonografie; Elastografie; Computertomografie; Magnetresonanztomografie; diffusionsgewichtete Bildgebung; Positronenemissionstomografie